Ivabradine use in pregnant women—treatment indications and pregnancy outcome: an evaluation of the German Embryotox database - Maria Hoeltzenbein; Marie-Louise Lehmann; Evelin Beck; Katarina Dathe; Christof Schaefer (European Journal of Clinical Pharmacology, 2021)
Purpose Ivabradine has been approved for the treatment of chronic heart failure and chronic stable angina pectoris in Europe. Based on adverse outcomes of reproductive animal studies and the lack of human data, ivabradine is considered contraindicated during pregnancy. The aim of this observational study is to analyse ivabradine use before and during pregnancy. Methods We evaluated all ivabradine-related requests to the German Embryotox Institute from 2007 to 2019. Exposed pregnancies were analysed as to their outcome. Results Off-label use for supraventricular tachycardia was frequent in women of childbearing age. Of 38 prospectively ascertained pregnancies with ivabradine exposure and completed follow-up, 32 resulted in live births, 3 in spontaneous abortions, and 3 were electively terminated. One neonate presented with major birth defects (atrial septal defect and cleft palate). In 33/38 patients, ivabradine was discontinued after confirmation of pregnancy without cardiac deterioration and 5/38 women continued ivabradine throughout pregnancy. In addition, there were 3 retrospectively reported pregnancies including one major birth defect (tracheal atresia). Conclusion This case series represents the largest cohort of ivabradine-exposed pregnancies, published so far. According to our findings, ivabradine appears not to be a major teratogen. However, established drugs of choice with strong evidence of low risk for the unborn should be preferred in women planning pregnancy. After inadvertent exposure during pregnancy or lack of treatment alternatives, fetal ultrasound for structural anomalies and growth restriction is recommended. In addition, close monitoring is necessary in pregnant women with supraventricular arrhythmias or cardiac disease.

E-vapor aerosols do not compromise bone integrity relative to cigarette smoke after 6-month inhalation in an ApoE–/– mouse model - Marie K. Reumann; Jenny Schaefer; Bjoern Titz; Romina H. Aspera-Werz; Ee Tsin Wong; Justyna Szostak; Victor Häussling; Sabrina Ehnert; Patrice Leroy; Wei Teck Tan; Arkadiusz Kuczaj; Christof Audretsch; et al. (Archives of Toxicology, 2020)
Cigarette smoke (CS) exposure is one of the leading risk factors for human health. Nicotine-containing inhalable products, such as e-cigarettes, can effectively support tobacco harm reduction approaches. However, there are limited comparative data on the effects of the aerosols generated from electronic vapor products (e-vapor) and CS on bone. Here, we report the effects of e-vapor aerosols and CS on bone morphology, structure, and strength in a 6-month inhalation study. Eight-week-old ApoE –/– mice were exposed to aerosols from three different e-vapor formulations—CARRIER (propylene glycol and vegetable glycerol), BASE (CARRIER and nicotine), TEST (BASE and flavor)—to CS from 3R4F reference cigarettes at matched nicotine concentrations (35 µg/L) or to fresh air (Sham) ( N = 10 per group). Tibiae were analyzed for bone morphology by µCT imaging, biomechanics by three-point bending, and by histological analysis. CS inhalation caused a significant decrease in cortical and total bone volume fraction and bone density relative to e-vapor aerosols. Additionally, CS exposure caused a decrease in ultimate load and stiffness. In contrast, bone structural and biomechanical parameters were not significantly affected by e-vapor aerosol or Sham exposure. At the dissection time point, there was no significant difference in body weight or tibia bone weight or length among the groups. Histological findings revealed microcracks in cortical bone areas among all exposed groups compared to Sham control. In conclusion, because of the bone-preserving effect of e-vapor aerosols relative to CS exposure, e-vapor products could potentially constitute less harmful alternatives to cigarettes in situations in which bone health is of importance.

Risk estimation of fetal adverse effects after short-term second trimester exposure to non-steroidal anti-inflammatory drugs: a literature review - Katarina Dathe; Stefanie Hultzsch; Lucas William Pritchard; Christof Schaefer (European Journal of Clinical Pharmacology, 2019)

Exposure to cox-2 inhibitors (coxibs) during the first trimester and pregnancy outcome: a prospective observational cohort study - Katarina Dathe; Stephanie Padberg; Stefanie Hultzsch; Luisa-Maria Köhler; Katja Meixner; Anne-Katrin Fietz; Tatjana Tissen-Diabaté; Reinhard Meister; Christof Schaefer (European Journal of Clinical Pharmacology, 2018)

Drug safety in pregnancy: the German Embryotox institute - Katarina Dathe; Christof Schaefer (European Journal of Clinical Pharmacology, 2018)